The Issue of Spiritual and Patriotic Education of Young Generation in the Scientific, Political and Literary Heritage of Central Asian Thinkers - U.N. , Khodjamkulov; K.S. , Makhmudov; A.M. , Shofkorov (International Journal of Psychosocial Rehabilitation, 2020)
The complex of material and aesthetic values that have been left to humanity since ancient times is called cultural heritage. As society changes, its culture and type will alter, but cultural development will not cease, an ancient culture will not disappear, and cultural heritage and traditions will be preserved. Each new generation does not inevitably create the basis of material and spiritual culture but receives cultural values created by ancestors. Central Asia is known for its eminent thinkers in the world community. A comprehensive study of the rich cultural heritage of these philosophers is a key task of today’s scientists. The study of the legacy of these thinkers was banned during the Soviet era. They were treated unfairly from the point of view of communist ideology. The social and political alterations associated with the collapse of the Soviet Union in the last decade of the 20th century have radically changed the attitude towards the legacy of thinkers. Currently, their scientific heritage is being comprehensively researched. Particularly, the scientific, political, and literary heritage of Central Asian thinkers depends upon a particular study of the spirituality and patriotism of young people. This is significant in bringing up the youth of the present time as highly moral and patriotic people.